Text Readability Level Investigation about Biology Subjects-related Units in 'Science 7 Textbook' - Şeyda Gül; Pınar Deniz Kargin (Journal of Science Learning, 2021)
This study investigates text readability level investigation about biology subjects-related units in 'Science 7 Textbook'. A document analysis method was used in this study based on a qualitative research approach. The textbook, which has been used since the 2019-2020 academic year, has been selected as the study material. In the textbook, a total of 15 texts were randomly determined from two units related to biology subjects, one for each of the learning outcomes specified in the 2018 Science Course Curriculum. In calculating the readability levels of the texts, the 'Ateşman Readability Formula' was used. The findings obtained as a result of the analysis showed that the overall readability levels of the texts in both units were in the 'medium difficulty' category. Furthermore, when the findings of each unit were examined on a subject basis, it was determined that the texts belonging to all of the topics included in both units (Cell and Divisions, Reproduction, Growth and Development in Living Beings) were found in the 'medium' category. These findings were interpreted as the science textbook prepared for the seventh grade for the student level in terms of readability.